Promotional Materials Management System for Improving Brand Awareness in Part Sales, Marketing and Logistic Division (H3) Of Pt. Daya Adicipta Motora - Pratama, Muhamad Adam; Wiralaga, Nenda Syafar; Kurnianto, Ryan Yusuf; Bunyamin, Hasbah; Nugraha, Ucu (International Journal of Psychosocial Rehabilitation, 2020)
Abstract: PT. Daya Adicipta Motora is a leading Honda motorcycle and spare parts distributor in West Java, contributing to PT. Astra Honda Motor. This company consists of three divisions, H1 (Motorcycle sales), H2 (Maintenance), and H3 (Spareparts Sales). Nowadays, spare part business is growing rapidly, leading to tighter business competition. This condition demands good performance from the main dealer to all its network. One of the demands is the high sales target. In order to anticipate this condition, promotion media is heavily required as a medium to introduce the product to the customer. The current promotional materials are banners, flag chains, and educational posters provided by PT. Astra Honda Motor. However, the distribution of these materials still faces a problem. This problem arises from both the main dealer and the network. It emerges in the form of inequitable distribution. From the network’s side, the problem emerges due to the lack of information regarding available promotional materials and manual distribution. Therefore, a web-based application is developed using the Unified Software Development Process (USDP). It aims to solve the problem mentioned earlier, and it also possesses value-added due to its feature that can help to manage promotional materials. The case study in developing this application was conducted in Part Sales, Marketing, and Logistic Division (H3) of PT. Daya Adicipta Motora. Using this application, it is expected to be able to help Part Sales, Marketing, and Logistic Division (H3) of PT. Daya Adicipta Motora to manage the promotional materials.